Evaluacón de parámetros productivos y reproductivos de tres líneas de cuyes utilizando empadre continuo hasta el 3er parto en Kotosh 2013 - Alejos Patiño, Italo (2017)
The study was conducted in central production Kotosh Hermilio Valdizan National University , in order to promote the proper management of guinea pig small animals in different production to improve productive and reproductive indices in the various existing lines in our to standardize production standards in regard to phenotype and genotype for case 3 pure lines Peruvian, Andean, Inti Y was evaluated against what is in our common environment, obtaining results for the Peruvian line with results very favorable relative to the other lines, with , however with regard to birth weight line was the witness gave better results 86 g .on average with respect to the other with lower weights , however in general terms the Peruvian exceeds all respects as larger number of offspring per litter is 2.5 per litter being , lower mortality at weaning pups more meat appearance, uniformity progeny from the control that had the parents other pigmentations.